Private international law - Hill, David (Lecturer in law) (Edinburgh law essentials., 2014)
'Private International Law Essentials' is an invaluable study guide for students. It provides up-to-date, concise and comprehensive coverage of private international law and is the ideal text for students who come new to the subject and for those preparing for exams. This book is also an excellent resource for those who need ro refresh or update their knowledge.